Mechanical properties of bone in compression - Tan, Marcus Kheng Yew. (2011)
The objective of this project is to evaluate the difference in mechanical properties of the porcine femur and humerus bones using compression testing. Cylindrical samples were cored from slabs of porcine femur and humerus bone using a diamond coring tool. Compression tests were performed using a strain rate of 0.04/s with a 1000 N load cell. Stress-strain curves were derived from force-deformation curves and the mechanical properties such as the ultimate tensile stress and Young‟s modulus were determined. The mechanical properties of Young‟s modulus and ultimate stress were plotted against apparent density and their correlation coefficients were determined using linear regression analysis. For porcine femur, slight correlation (R2 = 0.297) was observed between Young‟s modulus and apparent density while strong correlation (R2 = 0.818) was seen between ultimate stress and apparent density. On the other hand for porcine humerus, moderate correlations were found between ultimate stress and apparent density (R2 = 0.666) while strong correlation (R2 = 0.896) was seen between Young‟s modulus and apparent density. A good correlation (R2 > 0.5) of mechanical properties with apparent density implies that the protocols used are acceptable.